Influence of central wavelength of pump source and pump direction on transverse mode instability threshold of fiber laser. (July 2023) - Wan, Yingchao; Xi, Xiaoming; Shen, Yanlong; Wang, Xiaolin
Highlights: Transverse Mode Instability threshold can be enhanced when the central wavelength of the pump source deviates from 976 nm. TMI threshold of fiber lasers with bi-pumping structure is in turn greater than that of counter-pumping, co-pumping. TMI threshold of bi-pumping structure can be greater, equal to, or less than the sum of co-pumping and counter-pumping. The counter-pump injection power in the TMI threshold of bi-pumping is larger than the TMI threshold of counter-pumping. Abstract: In high-power ytterbium ion-doped fiber lasers where the output power is limited only by the transverse mode instability (TMI), the TMI threshold of fiber lasers with counter-propagating pumping (counter-pumping) structure is usually greater than that of co-propagating pumping (co-pumping), and bidirectional pumping (bi-pumping) is in turn greater than that of counter-pumping. In order to increase the TMI threshold, we optimized the central wavelength of the pump source to a bi-pumped fiber laser oscillator. In the experiment, we found that only the central wavelength of the pump source is changed in the same fiber laser, and the TMI threshold of the bi-pumping structure is sometimes greater than the sum of the TMI thresholds at the time of only co-pumping and only counter-pumping, sometimes approximately equal to, sometimes less. In addition, an interesting phenomenon was also reported that the counter-pump injection power of the fiber laser in the TMI threshold of bi-pumping is larger than the TMI threshold of only counter-pumping. Using the fiber laser simulation software, we explained the above phenomenon from the two directions of thermal effect and population reverse ratio in the active fiber. These research results are helpful to further optimize each device parameter of fiber laser and achieve higher power output.